Identification of two minor subunits in the pilus of Haemophilus influenzae. - McCrea, K W (1997)
Haemophilus influenzae type b (Hib) organisms produce pili, which mediate attachment to human cells and are multimeric structures composed of a 24-kDa subunit called pilin or HifA. Although pili from other organisms contain additional proteins accessory to pilin, no structural components other than pilin have been identified in Hib pili. Previous analysis of a Hib pilus gene cluster, however, suggested that two genes, hifD and hifE, may encode additional pilus subunits. To determine if hifD and hifE encode pilus components, the genes were overexpressed in Escherichia coli and the resulting proteins were purified and used to raise polyclonal antisera. Antisera raised against C-terminal HifD and HifE fragments reacted with H. influenzae HifD and HifE proteins, respectively, on Western immunoblots. Western immunoblot analysis of immunoprecipitated Hib pili demonstrated that HifD and HifE copurified with pili. In enzyme-linked immunosorbent assays, antisera raised against a recombinant HifE protein that contained most of the mature protein reacted more to piliated Hib than to nonpiliated Hib or to a mutant containing a hifE gene insertion. Immunoelectron microscopy confirmed that the HifE antiserum bound to pili and demonstrated that the antiserum bound predominantly to the pilus tips. These data indicate that HifD and HifE are pilus subunits. Adherence inhibition studies demonstrated that the HifE antiserum completely blocked pilus-mediated hemagglutination, suggesting that HifE mediates pilus adherence.